Multidimensional self-concept structure for preadolescents with mild intellectual disabilities - A hybrid multigroup-MIMC approach to factorial invariance and latent mean differences - Marsh, H; Tracey, D; Craven, R (2006)
Confirmatory factor analysis of responses by 211 preadolescents (M age = 10.25 years,SD = 1.48) with mild intellectual disabilities (MIDs) to the individually administered Self Description Questionnaire I-Individual Administration (SDQI-IA) counters widely cited claims that these children cannot differentiate multiple self-concept factors. Results provide clear support for the a priori eight-factor solution, modest correlations between the factors (Mdn r =.38), substantial reliabilities (Mdn =.90), and invariance of the factor solution over gender, age, and educational placement (regular vs. special, segregated classes). Also introduced is a new hybrid compromise between multigroup and multipleindicator-multiple-cause (MIMIC) approaches to latent mean differences. Consistent with a priori predictions, preadolescents with MIDs have lower self-concepts in segregated classes than in regular classes for three academic self-concept scales (reading, math, and general-school) and, to a lesser extent, peer relationships and global selfesteem, but not for the other three nonacademic components of self-concept (physical, appearance, and parent relationships). © 2006 Sage Publications.